EXPLORING THE TYPES OF CONVERSION IN LINGUISTICS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This study explores the linguistic phenomenon of conversion across various grammatical categories, focusing on its types, semantic implications, and syntactic considerations. Conversion, characterized by the transformation of words between different lexical categories without overt morphological changes, serves as a significant area of inquiry in linguistics. The investigation delves into five primary types of conversion: noun to verb, verb to noun, adjective to noun, noun to adjective, and adjective to verb. Each type is examined in terms of its semantic extensions, syntactic roles, and linguistic motivations. Through a comprehensive analysis, this study aims to deepen our understanding of conversion phenomena and their implications for language structure and usage.